PENERAPAN METODE SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) DENGAN PERMAINAN â€œPOS PELANGIâ€ UNTUK MENINGKATKAN KEMAMPUAN MENYIMPULKAN ISI CERITA ANAK YANG DIBACA - Atikah, Iis; Iswara, Prana Dwija; Djuanda, Dadan (Jurnal Pena Ilmiah, 2017)
This study aims to improve studentâ€™s ability in concluding the contents of the story. Based on the result of research that has been done in class V A SDN Cirayun show that student still have difficulty in summing up the story content. These problems occur because the management of the class is not optimal, and the use of learning methods that are less varied. The overcome these problems, the researcher determines the action by applying the Survey, Question, Read, Recite, Review (SQ3R) method with the rainbow post game. In cycle I, the result of teacher performance planning reached 83,3%, 90,4% cycle II, and third cycle 97,6%. Meanwhile, student activity in cycle I reached 12%, 72% of cycle II, and 88% of cycle III. While the result of student learning which got the complete category continue to exprecience good improvement, initially in cycle I only 5 students (36%), cycle II 18 students (72%), and in cycle III increased to 23 students (92%). Thus, it can be concluded that the application of SQ3R method with rainbow post game can improve the ability of grade V A students of SDN Cirayun in concluding the story content of children who read.